In-focus ABG interpretation (Carrollton : HSTN, 2000)
Arterial blood gases are an invaluable tool in assessing ventilation, acid-based balace, and oxygenation. Emphasizing that a crucial skill in the analysis of lab values is the ability to differentiate between treating the patient and treating the numbers, this video reviews ABG technique, interpretation of results, and interventions.
Keywords: Nursing -- methods